The Influence of Basic Psychological Needs Satisfaction on Well-Being: A Study on Higher Education Faculty in the New Normal - Balajadia, Janine Marie (Archīum Ateneo, 2023)
The world enters a new normal in response to the crisis brought on by the COVID-19 pandemic. This new normal has its unique challenges and opportunities for the faculty as physical campuses gradually re-open for teaching and learning. Although a growing amount of research has shown a relationship between the extent of basic psychological needs satisfaction and the state of well-being in diverse populations, studies focused on the faculty in the new normal remain limited. An online survey of 100 faculty from an institution of Catholic higher education in the Philippines was thereby carried out in the latter half of 2022 to examine such a relationship. The results of this study showed that satisfying the basic psychological needs of the faculty during the new normal can contribute significantly to their well-being. These results can inform higher education institutions on how they can best support their faculty in the new normal and promote student learning.